Programa de rehabilitación pulmonar en adultos mayores con enfermedades respiratorias crónicas asilados en el centro gerontológico en la ciudad Babahoyo en el primer semestre del 2017. - Rosado Hurtado, Gabriela Fernanda (2017)
Older adults who suffer from chronic respiratory diseases, and who suffer from clinical signs of dyspnea, productive or not, productive fatigue, exercise intolerance, must enter a pulmonary rehabilitation program, as it would help them to improve their physical health, Emotional and psychological. The present research study was developed at the Gerontological Center of the city of Babahoyo, which houses 50 elderly permanently and 50 older adults who receive partial services; Is performed in the need to determine the efficacy of pulmonary rehabilitation in the treatment of chronic respiratory diseases in the elderly, through the application of scientific methods, it is intended to deduce and relate the information provided in the investigation, through the collection of Data with the objective of establishing behavioral patterns of pulmonary rehabilitation and its incidence in chronic respiratory diseases, until we can prove the hypotheses that are raised in the present investigation. The research reveals a scientific contribution in the field of diagnosis and treatment of pulmonary diseases, it also has a large compendium of theories and conceptualizations of relevant sources of scientific production, becoming a starting point for the construction of new theories. We analyzed 30 clinical histories. The mean age of the patients was 78. 73% of the older adults belonged to the masculine gender, by means of spirometric techniques, the degree of obstruction present in this age group could be evaluated